Differences in Force Levels, Word Recognition in Quiet, Sentence Reception Threshold in Noise, and Subjective Outcomes for a Bone-Anchored Hearing Device Programmed Using Manufacturer First-Fit, Aided Sound-Field Thresholds and Programmed to DSL-BCD Using a Skull Simulator - Voss, Adam; Brockmeyer, Alison; Valente, Michael; Pumford, John; Wick, Cameron C.; Durakovic, Nedim (Journal of the American Academy of Audiology, 2021)
Background Best practice guidelines for verifying fittings of bone-anchored hearing devices (BAHD) recommend using aided sound-field thresholds (ASFT), but express caution regarding the variables impacting obtaining valid and reliable ASFTs.1 Recently, a skull simulator was introduced to facilitate programming BAHD devices in force level (FL) to desired sensation level-bone conduction devices (skull simulator/DSL-BCD)23 targets in a hearing aid analyzer. Currently, no evidence is available reporting if differences in measured FL using the manufacturer first-fit (FF) and word recognition in quiet, sentence reception threshold in noise, and subjective outcomes are present for a BAHD programmed using ASFT versus programmed using skull simulator/DSL-BCD targets.Purpose The aim of this study was to examine if significant differences were present in FL using the FF and word recognition in quiet at 50 and 65 decibel of sound pressure level (dB SPL), sentence reception threshold in noise and subjective outcomes using the abbreviated profile of hearing aid benefit (APHAB), and speech, spatial, and qualities of hearing (SSQ) between a BAHD fit using ASFT or skull simulator/DSL-BCD targets.Research Design A double-blind randomized crossover design with 15 adults having unilateral sensorineural hearing loss. All participants were successful users of the Cochlear America Baha 5.Data Collection and Analysis Baha Power 5 devices were fit using FF, ASFT, and skull simulator/DSL-BCD targets. Order of the three fitting strategies was randomly assigned and counter-balanced.Results No significant differences were found for a BAHD device programmed using ASFT versus skull simulator/DSL-BCD targets for consonant-nucleus-consonant words in quiet at 50 or 65 dB SPL, sentence reception threshold in noise, the APHAB or SSQ. There were, however, significant differences, at primarily 500 to 2,000 Hz in measured FLs between the FF, ASFT, and skull simulator/DSL-BCD targets at 50 and 65 dB SPL.Conclusions There were no significant differences in subject performance with two speech measures and subjective responses to two questionnaires for BAHD fittings using ASFT versus using skull simulator/DSL-BCD targets. Differences in FL between the three fitting strategies were present primarily at 500 to 2,000 Hz. Limitations of the study are highlighted along with situations where the skull simulator can play a significantly beneficial role when fitting BAHD devices.
Keywords: bone-anchored hearing device; Baha Power 5; skull simulator; DSL-BCD